In situ crack opening displacement growth rates of SiC/SiC ceramic matrix minicomposites. Issue 9 (August 2023) - Muir, C.; Swaminathan, B.; Musaffar, A.K.; McCarthy, N.R.; Almansour, A.S.; Pollock, T.M.; Kiser, J.D.; Smith, C.; Daly, S.; Sevener, K.
Abstract: In ceramic matrix composites, crack opening displacements (CODs) influence environmental degradation rates. As a result, strategies for extending CMC lifetimes are driven by understanding COD evolution. While many models describe COD growth, few experimental studies exist to validate their accuracy. In this work, it is experimentally demonstrated that significant amounts of CODs can deviate from the classical σ 2 dependence typically proposed in models. CODs of transverse matrix cracks were measured in situ via scanning electron microscopy, for four unidirectional SiC/SiC minicomposites with different fiber volume fractions and interfacial properties. Values were compared to predictions from well-established micromechanics models. Significant proportions of CODs ( > 45 % ) deviated from the canonical σ 2 growth rate, which is attributed to crack geometries and proximity to neighboring cracks. Additionally, large proportions of cracks grew slower than could be predicted by statistical variations of interfacial parameters; this is hypothesized to be a result of subsurface intact matrix content.